Glacial and periglacial geomorphology of the Boí Valley (Central Pyrenees) - Rubio-Felez, Alba; Oliva, Marc; Ventura, Josep (My University, 2025)
In recent years, knowledge of Late Pleistocene glacial evolution in the Pyrenees has become increasingly robust, as has its chronological framework, which has been revised and refined. However, the subsequent environmental evolution remains largely unknown. Within this context, the Boí Valley (Central Pyrenees) is a relatively understudied area. This study aims to improve our understanding of the behavior of Quaternary glaciers in the region, as well as the postglacial environmental changes that have occurred since the last Glacial Cycle. To this end, a 1:50,000-scale geomorphological map has been produced for the Boí Valley (247 km2), incorporating the main landforms identified through cartographic analysis and field observations. Based on the distribution of the most significant glacial and periglacial features, a relative and comparative chronological framework is proposed in relation to studies from nearby areas: (i) a phase of maximum valley glaciation, likely corresponding to the Local Last Glacial Maximum of the last Glacial Cycle; (ii) a phase in which valley glaciers retreated to higher elevations; (iii) a phase dominated by cirque glaciers; and (iv) a deglaciation phase that has shaped the current alpine landscape. Today, no glaciers remain in the study area. Postglacial environmental dynamics are interpreted within three altitudinal zones: the subnival zone (~ 850–1800 m), characterized by fluvial and alluvial processes, deposits from various types of mass movements on valley slopes, and widespread forest cover on slopes; the nival zone (~ 1800–2400 m), where snow persists for 5–7 months each year and drives early cryonival activity; and the periglacial zone (~ 2400–3000 m), where active processes are associated with seasonal frost, frost weathering, and the movement of rock glaciers and protalus lobes. Sporadic permafrost is also present in this high-altitude environment. Future research should aim to establish an absolute chronology of the region's glacial and deglacial history.
Keywords: boí valley; central pyrenees; geomorphological map; glaciation; periglacial processes